Traditions and Transformations of Qur’anic Education in Two Pesantren - Muhammad Jamil (Insitut Muslim Cendekia, 2025)
This study examines the dynamics of tradition and transformation in Qur’anic education in two types of pesantren in East Java: the traditional (salaf) Langitan pesantren and the modern Al-Muhibbin pesantren. The study is driven by the urgency to critically assess how traditional religious institutions respond to socio-cultural changes that affect the transmission, authority, and meaning of Qur’anic education. The research aims to identify the forms of preservation and shifts in Qur’anic educational practices, while analyzing the ideological framing of modernization within the pesantren context. A qualitative approach is employed, utilizing participant observation, in-depth interviews, and document analysis. The findings reveal that the salaf pesantren consistently maintain classical educational structures based on sanad, ritual, and scholarly authority, whereas the modern pesantren develop adaptive innovations that are not always accommodating of traditional values. The novelty of this study lies in its critical reading of the transformation process, which is often simplistically equated with progress, as well as in its conceptual proposal of a synthesis between value preservation and pedagogical innovation. This research contributes theoretically to Islamic education studies by emphasizing the necessity of epistemic continuity amid educational change.